2021
DOI: 10.22159/ajpcr.2021.v14i10.42753
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Antimicrobial Susceptibility Pattern of Microorganisms Causing Intra-Abdominal Infections at Tertiary Care Hospital of Northern India

Abstract: Objective: The objective of the study is to find out the resistance pattern of pathogenic organisms isolated from intra-abdominal infection (IAI). Methods: A total of 500 samples were collected from suspected IAIs of patients reporting to the hospital and cultured. Identification of the isolates was done using standard identification protocol. Antimicrobial susceptibility was performed by Kirby-Bauer disc diffusion method and interpretation was done using Central Laboratory Standard Institute guidelines. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…However, many of the similar types of bacteria as identified in this study are reported to cause of abortions, as Salmonella enterica serovars including S. Dublin in cattle [23][24][25], Aeromonas species in equids [26] and bovines [27], Enterobacter agglomerans in equids [28,29], Moelerella wisconsensis in bovines [30,31], Xenorhabdus bovienii and X. poinarii in bovines [30], K. pneumoniae in cattle [27]. However, K. varians identified as cause of abortion and or me- [11,12,27,30,31,34,35] but some like K. varians and V. alginolyticus have rarely been associated with bovine infections but reported in human as opportunistic pathogens. Similar types of bacteria have been reported in vaginal tract of apparently healthy sows [35] and a closely related animal, mithun (Bos frontalis), to buffaloes [34] indicating that the bacteria identified in the present study might be opportunistic pathogens of reproductive tract.…”
Section: Discussionmentioning
confidence: 80%
“…However, many of the similar types of bacteria as identified in this study are reported to cause of abortions, as Salmonella enterica serovars including S. Dublin in cattle [23][24][25], Aeromonas species in equids [26] and bovines [27], Enterobacter agglomerans in equids [28,29], Moelerella wisconsensis in bovines [30,31], Xenorhabdus bovienii and X. poinarii in bovines [30], K. pneumoniae in cattle [27]. However, K. varians identified as cause of abortion and or me- [11,12,27,30,31,34,35] but some like K. varians and V. alginolyticus have rarely been associated with bovine infections but reported in human as opportunistic pathogens. Similar types of bacteria have been reported in vaginal tract of apparently healthy sows [35] and a closely related animal, mithun (Bos frontalis), to buffaloes [34] indicating that the bacteria identified in the present study might be opportunistic pathogens of reproductive tract.…”
Section: Discussionmentioning
confidence: 80%